ANO-catalyzed multicomponent synthesis of 3-nitroalkyl-N-substituted pyrroles - Luiz H. Dapper; Viviane T. Mena; Márcio S. Silva; Filipe Penteado; Eder J. Lenardão (Tetrahedron Green Chem)
A sustainable and atom-economic method was developed to prepare functionalized nitroalkyl pyrroles through a multicomponent reaction involving anilines, hexane-2,5-dione, and β-nitrostyrene derivatives. Ammonium niobium oxalate (ANO) was used as a cheap and reusable catalyst with ethanol as an eco-friendly solvent. A total of twenty-five N-substituted nitroalkyl-functionalized pyrroles were prepared in moderate to excellent yields (up to 93%). The method was successfully applied to electron-rich and electron-poor anilines, as well as to butylamine, simply by using a telescoping procedure (one-pot). Besides, the easy transformation of the obtained product in a primary amine was demonstrated.